Pengaruh Variasi Bahan Baku Terhadap Rasio C/N dari Potensi Biogas Campuran Kotoran ayam dan Eceng Gondok : Pengaruh Variasi Bahan Baku Terhadap Rasio C/N dari Potensi Biogas Campuran Kotoran ayam dan Eceng Gondok - Sahrur Ramadan (Institut Riset dan Publikasi Indonesia, 2025)
This study aims to determine the optimal C/N (carbon/nitrogen) ratio of a mixture of chicken manure and water hyacinth in the anaerobic fermentation process, as well as to evaluate the potential for biogas and electricity production with and without the use of a starter. In this experiment, a mixture of 300 kg of chicken manure and 200 kg of water hyacinth, with an additional 75 kg of starter, was used to achieve a more ideal C/N ratio. The fermentation process was carried out in two scenarios: one with a starter and one without a starter, to compare the results. The analysis results show that the use of a starter significantly increased the volume of biogas produced, which was 89.06 m³, compared to 70 m³ produced without a starter. In addition, the potential for electricity generation also increased significantly, from 329 kWh without a starter to 418 kWh with a starter. The biogas production increased by 27.23% with the use of a starter. These findings suggest that the use of a starter not only increases the volume of biogas but also improves energy conversion efficiency, making it an effective method to enhance anaerobic fermentation outcomes and achieve a more ideal C/N ratio, which in turn can optimize renewable energy production from organic materials.